Impact of Credit Advanced by Zarai Taraqiati Bank Limited on the Income of Farmers in the Livestock Sector in District Dir Lower, Khyber Pakhtunkhwa - Ahmad, Ishaq; Ahmad, Sohail (Journal of Development and Social Sciences, 2024)
This study examines the impact of credit advanced by ZTBL on the income of farmers in the livestock sector in district Dir Lower, KP. A multistage random sampling technique was employed to randomly select district Dir Lower in the first stage, followed by four tehsils. The Yamane formula and Proportional allocation technique were used to randomly select a sample size of 298 farmers from a total of 1200 loanee farmers. Data were collected through a semi-structured questionnaire and personal interviews during 2017–2020. The data were analyzed using descriptive and inferential statistics. A multiple linear regression model was applied to quantitatively determine the impact of ZTBL credit on the income of farmers in the livestock sector. The estimated results show that ZTBL credit has a positive and statistically significant impact on farmers' income in the livestock sector. Additionally, other variables, such as age, education level, family size, farm size, livestock holdings, and farming experience, also show a positive and statistically significant relationship with farmers' income. The study recommends that ZTBL should introduce interest-free loans based on Islamic partnership, recognize its friendly policy regarding collateral requirements, and simplify the credit procedure to facilitate credit access. Furthermore, the study suggests that ZTBL should increase its local branches to support farmers and increase their income.